The narrative voice in the Theogony of Hesiod - Stoddard, Kathryn.
1 online resource (xv, 206 pages)
Keywords: This volume offers analysis of the narratological structure of the Theogony with the purpose of elucidating a major, unifying theme in this poem: the relationship between the divine and mortal realms. The techniques of narratology are herein employed to support the argument that Hesiod portrays the cosmos as sharply divided between gods and men. The Theogony should therefore be read as a didactic poem explaining primarily the position of man vis-à-vis the gods. The first half of this book discusses relevant scholarship and introduces the theme of relationship of gods to men in the Theogony . The second half of the book discusses how Hesiod employs Character-Text, Attributive Discourse, Embedded Focalization, Anachrony, and Commentary to achieve his didactic purposes.